The Public Perception Toward the E-Medicine (Internet) Usage At Sultanah Bahiyah Hospital Alor Star, Kedah - Elrekie, Abdel Rahman Mahmud A. (2008)
The general purpose of this study was to find out whether a relationship between user skill, user knowledge and e-medicine performance. This study was determining the review of literature about user skill, user knowledge and e-medicine performance model as the underpinning theory to the theoretical framework. This study presented the clear description of e-medicine as technology adoption to doctor and patient as user of the system. The significance of this research was to apply the conceptual of e-medicine in the user context. This study proposes to identify the global IT improvement towards the usage of e-medicine technology and to identify the magnitude perception among patient and medical profession toward the usage of e-medicine technology. Independent sample T-test analysis was conducted to examine user skill and user knowledge to e-medicine performance among doctor and patient. The study confirmed that doctor and patient should improve their skill and knowledge of e-medicine. These studies strongly recommend doctor and patient in other to improve their skill and knowledge of e-medicine. Based on skill between doctor and patient has insignificant different.